Psychological Consequences of Social Isolation During COVID-19 Outbreak - Pietrabissa, Giada; Simpson, Susan G. (Frontiers in Psychology, 2020)
Perceived social isolation during the COVID-19 pandemic significantly has had an extraordinary global impact, with significant psychological consequences. Changes in our daily lives, feeling of loneliness, job losses, financial difficulty, and grief over the death of loved ones have the potential to affect the mental health of many. In an atmosphere of uncertainty, it is essential that clear and precise information is offered about the problem and how to manage it. In this contribution, a rationale is provided for an urgent call for a rapid response to the mental health impacts of COVID-19. Moreover, suggestions for individuals to regulate their emotions effectively and appropriately are provided.